Absence of Measles Virus Detection from Stapes of Patients with Otosclerosis. (January 2018) - Flores-García, María de Lourdes; Colín-Castro, Claudia Adriana; Hernández-Palestina, Mario Sabas; Sánchez-Larios, Roberto; Franco-Cendejas, Rafael
Objective: To determine molecularly the presence of measles virus genetic material in the stapes of patients with otosclerosis. Study Design: A cross-sectional study. Setting: A tertiary referral hospital. Subjects and Methods: Genetic material was extracted from the stapes of patients with otosclerosis (n = 93) during the period from March 2011 to April 2012. The presence of viral measles sequences was evaluated by the real-time reverse transcriptase polymerase chain reaction (RT-PCR). The expression of the CD46 gene was determined. Results: Ninety-three patients were included in the study. No sample was positive for any of 3 measles virus genes (H, N, and F). Measles virus RNA was not detected in any sample by real-time RT-PCR. CD46 levels were positive in 3.3% (n = 3) and negative in 96.7% (n = 90). Conclusion: This study does not support the theory of measles virus as the cause of otosclerosis. It is necessary to do more research about other causal theories to clarify its etiology and prevention.